PENGARUH VARIASI WAKTU SHOT PEENING TERHADAP STRUKTUR MIKRO DAN KEKERASAN PERMUKAAN PADA MATERIAL IMPLAN AISI 304 - Trio Nur Wibowo; Priyo Tri Iswanto; Bambang Hari Priyambodo; Nur Amin (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
AISI 304 stainless steel is a type of implant material with a relatively low cost. However, its mechanical properties need to be improved so it can compensate the AISI 316L and titanium alloy materials. Fatigue characteristic is also one of the important criteria that must be evaluated in order to achieve overall service performance when the material is under dynamic loads. The hardness surface and the nano-structures formation can delay the propagation of fatigue crack initiation and can reduce the corrosion rate. This study is conducted to determine the changes in microstructure and hardness of AISI 304 for shot peening process. The surface treatment by shot peening process is performed by setting the variation of the shooting time of 0, 5, 10, 20, 30 and 40 minutes at a shooting pressure of 7 bar using the Steel Shot diameter of 0.6 mm with a hardness of 40-50 HRC. The distance between the nozzle and the specimen surface is set at 100 mm. The microstructure is analyzed by optical microscope with a magnification of 100 times and photographed using optilab, which is connected to a computer. Surface hardness is tested using a Micro Vickers with indentation load of 10 grams for 10 seconds. The results show that refined microstructure layer is formed in the shot peening surface and the hardness is also increased gradually as well as shot peening time of 0, 5, 10, 20, 30 and 40 minutes. This also increase the hardness number of 241, 404, 418, 437, 481 and 496 VHN. To sum up, the shot peening can be used to refine the grain and to increase the hardness. Keywords: AISI 304, shot peening, microstructure, Vickers hardness